Pelvic floor reconstruction after extralevator abdominoperineal excision of the rectum: a literature review - V. S. Belyaev; Y. A. Dykhno; A. A. Nesytyh (Сибирский онкологический журнал, 2020)
The purpose of the study was to analyze studies reporting pelvic floor reconstruction after extralevator abdominoperineal excision for rectal cancer, reconstruction options, including advantages and disadvantages.Material and Methods. A literature search was performed using the Medline, Embase and Cochrane Library databases. Randomized clinical studies reporting the pelvic floor reconstruction after extralevator abdominoperineal excision of the rectum were evaluated.Results. Although many surgical options are available for the management of perineal wounds after cylindrical abdominoperineal extirpation of the rectum, treatment remains challenging. Primary perineal defect closure is a simple and economical way to close a wound; however it has a high rate of perineal wound complications with occurrence of perineal hernia. Although various options of myo- and alloplastic reconstruction have several advantages, they are more labor-and cost-intensive.Conclusion. There is a lack of randomized trials reporting the closure of the perineal defect after extralevator abdominoperineal extirpation of the rectum. There remains no consensus on which management strategy is superior; therefore, further studies are needed.